Experimental investigation of melting behavior of PCM by using coil heat source inside cylindrical container - M. Tayssir; S.M. Eldemerdash; R.Y. Sakr; A.R. Elshamy; O.E. Abdellatif (Journal of Electrical Systems and Information Technology, 2017)
The use of a latent heat storage system by using phase change materials (PCMs) is an effective method of storing thermal energy. This paper is carried out to study the melting behavior of PCM experimentally. The PCM used in the present study is paraffin wax and the heat transfer fluid, HTF is water. A test rig has been designed and constructed to store thermal energy in PCM contained in a vertical cylinder of 300 mm inner diameter and 600 mm height. A copper helical coil of 100 mm outer diameter and 300 mm height is fitted concentrically inside the cylinder and HTF is passed upward through the coil. Experiments were performed for different inlet temperatures of HTF 70 °C, 80 °C and 90 °C and for different volume flow rates 5 lpm, 10 lpm and 15 lpm. The transient variation of the molten fraction, the percentage of thermal energy storage and the average Nusselt number are obtained. A significant effect of the inlet HTF temperature more than that of volume flow rate on the paraffin melting process is observed. Also, empirical correlation for the molten fraction and percentage of heat stored are deduced in terms of the operating conditions.